2021
DOI: 10.1111/mcn.13298
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐household double burden of overweight/obesity and anaemia: Evidence from 49 low‐and middle‐income countries

Abstract: Globally, overweight/obesity is rising rapidly while anaemia persists. Nevertheless, evidence on their coexistence at the household level remains limited. Using data from the Demographic and Health Surveys, we quantified the magnitude, distribution and inequalities (i.e., estimates by wealth, education level and residence) in the intrahousehold double burden (DBM) of overweight/obesity and anaemia among mothers and their children under-5 living in 49 low-and middle-income countries (LMICs). The pooled prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…This study indicated that reproductive women with a primary level of education were negatively associated with co-occurrence of OWOB and anemia compared to women with no education. Even though, there are some literatures [ 17 , 53 ], stated that women who attain a higher level of education were more likely to develop co-occurrence of overweight/obesity and anemia, our finding revealed that the odds of co-occurrence of OWOB and anemia among women with a primary level of education was lower by 14% than non-educated. This might be because reproductive women who are educated are expected to get more information from different sources about appropriate dietary intake and health care services regarding the co-occurrence of overweight/obesity and anemia [ 54 ].…”
Section: Discussioncontrasting
confidence: 67%
“…This study indicated that reproductive women with a primary level of education were negatively associated with co-occurrence of OWOB and anemia compared to women with no education. Even though, there are some literatures [ 17 , 53 ], stated that women who attain a higher level of education were more likely to develop co-occurrence of overweight/obesity and anemia, our finding revealed that the odds of co-occurrence of OWOB and anemia among women with a primary level of education was lower by 14% than non-educated. This might be because reproductive women who are educated are expected to get more information from different sources about appropriate dietary intake and health care services regarding the co-occurrence of overweight/obesity and anemia [ 54 ].…”
Section: Discussioncontrasting
confidence: 67%
“…). It was also higher than estimates for the Americas region (21.6%) and for 49 LMICs combined (16.2%)(Irache et al, 2022b). The average prevalence of dyad level Demographic and Health Survey (DHS) reported that between 2009 and 2016, household level DBM (defined as a child with undernutrition [stunting, underweight or wasting] and a mother with overweight/ obesity) decreased from 10.7% to 7.2%(Mendoza-Quispe et al, 2021).…”
mentioning
confidence: 84%
“…(b) Distribution (%) of the coexistence of anaemia in the child (<2 years) and overweight (including obesity) in the mother. A, anaemia; OW, overweight (including obesity).level DBM (maternal overweight, including obesity, and child anaemia) was high (36.3%), when compared with estimates of household level DBM (defined as a mother with overweight/obesity and at least one of her children <5 years with anaemia or a mother with anaemia and at least one of her children with overweight/obesity or both combinations) for Peru (19.4%)(Irache et al, 2022b…”
mentioning
confidence: 94%
“…Moreover, some of these studies do not employ appropriate statistical method (ie, multilevel multinomial analysis) that accounts for hierarchical nature of data and polytomous nature of the nutritional status to identify determinants for each type of malnutrition 29–31. And other studies only focused either on overnutrition33 34 49–51 or undernutrition30 and did not assess the effect of some community-level factors (community-level poverty and community-level illiteracy) 29–31. Therefore, by taking into account the aforementioned methodological limitations, this study aimed to estimate the pooled burden and individual and community-level determinants of underweight, overweight and obesity among reproductive-age women in 33 sub-Saharan African countries.…”
Section: Introductionmentioning
confidence: 99%